Phylogeny and morphology of Premilcurensis gen. nov. (Pleosporales) from stems of Senecio in Italy - Tibpromma, Saowaluck; Promputtha, Itthayakorn; Phookamsak, Rungtiwa; Boonmee, Saranyaphat; Camporesi, Erio Camporesi; Yang, Jun-Bo; Bhakali, Ali H.; Mckenzie, Eric H. C.; Hyde, Kevin D. (Phytotaxa, 2015)
Premilcurensis senecionis gen. et and sp. nov. was collected on stems of Senecio sp. from Forlì-Cesena Province, Italy and is introduced in Phaeosphaeriaceae with the support of a unique combination of morphological characters and combined gene phylogenetic analyses. Premilcurensis is distinguished from other genera in Phaeosphaeriaceae in having fusiform to cylindrical, hyaline to yellow-green ascospores with 3–5 septa, and mucilaginous, wing-like appendages at the central septum. Phylogenies analyses show Premilcurensis as a distinct lineage from other genera in the family Phaeosphaeriaceae with high bootstrap support. A comprehensive description and micrographs of P. senecionis is provided and the new genus is compared with morphologically similar taxa.